When Is Teasing Abuse? A Grounded Theory of Teasing Among Mexican American Adolescent Dating Couples - Rueda, Heidi (Journal of interpersonal violence, 2025)
This study examined the use of teasing during observed videotaped interactions of Mexican American adolescent dating couples (N = 34; 15–17 years old) from an urban area of the Southwest United States. During the interaction task, couples discussed two relationship problems for 14 min and nearly all interactions (88.2%) contained teasing. In turn, we developed a grounded theory of teasing that delineated who initiated the teasing (boys/girls), teasing types, levels of severity of teasing incidents, youth’s motivations for teasing, and the resulting consequences of teasing in real time. We found that most teasing incidents were mild to moderately severe and that girls initiated teasing to a greater extent than boys. Regarding motives, youth used teasing to exert power during the interaction and/or to repair a problem in the relationship. Despite various types of teasing, the resulting consequences were hurt feelings, power struggles, and shame. Participants overtly stated that they desired improved communication. We recommend that socioemotional learning and dating violence prevention programs include teasing as part of conflict resolution skill sets and that these programs be informed by the cultural values of Mexican-origin youth.